Brand Image Antecedents to Enhance Consumer Trust - Runggu Besmandala Napitupulu (Dinasti International Journal of Management Science, 2023)
Research aims are to identify, analyze, and conclude the effect of price perception and product quality on brand image and consumer trust. The analytical technique applies a structural equation model lisrel software supported. The study results, namely the price perception and product quality partially have a positive effect on brand image. Price perception, product quality, and brand image have a partially positive effect on consumer trust. Brand image partially mediates the effect of perceived price and product quality on consumer trust. To enhance brand image, especially for emotional satisfaction, more specifically for the self-expression value, namely by increasing the price perception which is dominant among other exogenous variables. The price discount reflects price perception. This dimension is reflected dominantly by the rare discount. Retailers in Medan need to pay more attention to price discounts that are rare for users to enhance brand image. Increasing consumer trust, especially the retailer ability, more specifically institutional recognitions, namely by the dominant brand image among exogenous constructs. Retailers in Medan need to pay more attention to emotional satisfaction, especially the user self-expression value to enhance consumer trust.